Analysis of thermal behavior on concrete box-girder arch bridges under convection and solar radiation. Issue 7 (July 2016) - Wang, Yongbao; Zhan, Yulin; Zhao, Renda
The two-dimensional finite element method can be used to calculate the thermal field distribution of prestressed concrete bridge girders. However, this method is not appropriate for the concrete box-girder arch bridges, because they have different azimuth and dip angles at the top and bottom flanges along arch axis. Thus, an experimental and analytical study was conducted on a concrete box-girder arch bridge located in Guizhou, China, to investigate the thermal behavior under convection and the solar radiations. To determine the vertical temperature gradients, a two-dimensional plane finite element model was used to calculate the thermal field based on meteorological parameter methods. In addition, the three-dimensional beam finite element model was proposed to study the thermal stress and displacement of arch bridges using the vertical temperature gradients. Finally, the thermal behavior of the concrete box-girder arch bridges determined by the two-dimensional plane and three-dimensional beam finite element model was verified by three-dimensional solid finite element model.